2007
DOI: 10.1063/1.2826276
|View full text |Cite
|
Sign up to set email alerts
|

Improved operational lifetime of semiconducting polymer lasers by encapsulation

Abstract: We report polymer distributed feedback lasers with dramatically extended operational lifetimes by using a simple encapsulation process. The lasers are configured as surface emitting, two-dimensional distributed feedback lasers based on the polymer poly͓2-methoxy-5-͑2Ј-ethylhexyloxy͒-1,4-phenylene vinylene͔. The microstructure is transferred to the polymer surface through solvent assisted micromolding. Once encapsulated, a 2500-fold improvement in lifetime is demonstrated under ambient conditions, compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…The longest operating lifetime reported for a solid-state organic laser to date exceeds 2 × 10 7 pulses and was obtained from DFB lasers based on the fluorene copolymer Dow Red F [177]. Degradation can be mitigated by encapsulating the gain medium into other materials [187][188][189][190], a method that is commonly used to extend the operational lifetime of OLEDs by protecting from oxidation the emissive polymer layer and the metal contacts. The operating lifetime of lasers based on semiconducting conjugated polymers has been significantly prolonged by encapsulating the gain medium in either adhesives [187,188] or photopolymerizable resins [189] or other polymers [190].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longest operating lifetime reported for a solid-state organic laser to date exceeds 2 × 10 7 pulses and was obtained from DFB lasers based on the fluorene copolymer Dow Red F [177]. Degradation can be mitigated by encapsulating the gain medium into other materials [187][188][189][190], a method that is commonly used to extend the operational lifetime of OLEDs by protecting from oxidation the emissive polymer layer and the metal contacts. The operating lifetime of lasers based on semiconducting conjugated polymers has been significantly prolonged by encapsulating the gain medium in either adhesives [187,188] or photopolymerizable resins [189] or other polymers [190].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…Degradation can be mitigated by encapsulating the gain medium into other materials [187][188][189][190], a method that is commonly used to extend the operational lifetime of OLEDs by protecting from oxidation the emissive polymer layer and the metal contacts. The operating lifetime of lasers based on semiconducting conjugated polymers has been significantly prolonged by encapsulating the gain medium in either adhesives [187,188] or photopolymerizable resins [189] or other polymers [190]. The effectiveness of this approach was convincingly demonstrated in an experiment, in which the lifetime of a DFB MEH-PPV polymer laser increased from the 6 × 10 3 pulses to 1.6 × 10 7 pulses after encapsulation [187].…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…After this experiment, lasing could be observed as soon as the pump energy was increased for all the devices. As in the case of epoxy encapsulation [15] a blue-shift in the emission wavelength occurs during operation. The wavelength change was ~0.02 nm/10 5 pulses for the PMMA laser and ~5.2 nm/10 5 pulses for the COC lasers.…”
Section: Resultsmentioning
confidence: 99%
“…Bulović et al reported on organic semiconductor microcavity lasers encapsulated by evaporated organic and metal layers [14]. Richardson et al demonstrated encapsulation with an optical adhesive on top of organic semiconductor lasers [15]. Persano et al presented encapsulation utilizing a rapid prototyping technique and additionally gave an overview over present encapsulation schemes for organic photonic devices [16].…”
Section: Introductionmentioning
confidence: 99%
“…One possible way to achieve this is to embed the OS emitters within an appropriate polymeric host matrix, creating (when the OS gain molecules are of appropriate size) a nanocomposite. OS lasers have been reported using such an approach, showing extended photostability but to the detriment of the laser threshold performance [8,19]. Another way to improve the lifetime of an organic laser is to 'encapsulate', i.e.…”
Section: Introductionmentioning
confidence: 99%